2023
DOI: 10.5194/hess-27-3059-2023
|View full text |Cite
|
Sign up to set email alerts
|

A change in perspective: downhole cosmic-ray neutron sensing for the estimation of soil moisture

Daniel Rasche,
Jannis Weimar,
Martin Schrön
et al.

Abstract: Abstract. Above-ground cosmic-ray neutron sensing (CRNS) allows for the non-invasive estimation of the field-scale soil moisture content in the upper decimetres of the soil. However, large parts of the deeper vadose zone remain outside of its observational window. Retrieving soil moisture information from these deeper layers requires extrapolation, modelling or other methods, all of which come with methodological challenges. Against this background, we investigate CRNS for downhole soil moisture measurements i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 62 publications
3
7
0
Order By: Relevance
“…The largest difference between epithermal and thermal neutrons by applying the same correction occurs in respect to variations in absolute air humidity. We found that the linear regression slope, 0.0023, is less than half of that of epithermal neutrons and very close to the value recently found by Rasche et al (2023). The difference between the thermal and the epithermal neutron response to air humidity is likely linked to the generally higher production rate of thermal neutrons by epithermal neutron moderation compared to the thermal neutron absorption rate, which leads to a weaker response of thermal neutrons to variations in environmental hydrogen (Weimar et al, 2020).…”
Section: 1029/2023ea003483supporting
confidence: 86%
See 4 more Smart Citations
“…The largest difference between epithermal and thermal neutrons by applying the same correction occurs in respect to variations in absolute air humidity. We found that the linear regression slope, 0.0023, is less than half of that of epithermal neutrons and very close to the value recently found by Rasche et al (2023). The difference between the thermal and the epithermal neutron response to air humidity is likely linked to the generally higher production rate of thermal neutrons by epithermal neutron moderation compared to the thermal neutron absorption rate, which leads to a weaker response of thermal neutrons to variations in environmental hydrogen (Weimar et al, 2020).…”
Section: 1029/2023ea003483supporting
confidence: 86%
“…The observation data in Figure 4 demonstrate that the thermal neutrons response to air humidity is much smaller compared to epithermal neutrons. Using the recently published correction factor, α = 0.0021 m 3 /g (Rasche et al, 2023), which is very close the empirical observation from the buoy, the new correlation becomes R 2 = 0.01 for thermal neutrons and thereby confirms the insignificance of the temperature effect.…”
Section: Both Processes Scale Withsupporting
confidence: 82%
See 3 more Smart Citations